The Application of Genre-Based Approach and Deep Learning in Speaking Activities: An Analysis of the Eleventh-Grade English Textbook Published by the Ministry of Education, Culture, Research, and Technology in 2022 - Annisa Maharani; Widhiyanto (Universitas Islam Negeri Palopo, 2025)
The use of textbooks is common in Indonesia to support the learning process. However, textbooks do not always provide complete materials, so teachers must make adjustments to facilitate the learning process. Additionally, students face challenges when speaking or pronouncing English words. They are used to learn the written context of learning. By analyzing the textbook, especially in speaking activities, the text production process, which contains the Genre-based approach cycle, is examined. Furthermore, this current curriculum also supports the implementation of deep learning to check the deep understanding of students. The study aims to examine the application of the Genre-based Approach (GBA) and deep learning principles in the speaking activities of the “Bahasa Inggris: English for Change” textbook. Furthermore, the strengths and weaknesses of the speaking activities of this textbook are explained. This study employs qualitative research based on content analysis. The data is taken from Units 3-5 of this English textbook, especially for the speaking sections. There are a total of 32 activities that can be found based on the GBA learning cycles in Units 3 through 5. The principles of deep learning are applied to enhance the understanding of analysis for each indicator. However, some strengths and weaknesses can be found in the speaking activities of the chosen units. Further development of teaching materials is needed to create a more effective learning environment.